Social Worlds of Premodern Transactions : perspectives from Indian epigraphy and history - 'Social Worlds of Premodern Transactions' (Workshop) (2014 : Nehru Memorial Museum and Library); Gomes, Mekhola; Singh, Digvijay Kumar; Visvanathan, Meera; Nehru Memorial Museum and Library (Delhi : Primus Books, 2021)
Contributed articles presented at a workshop titled 'Social Worlds of Premodern Transactions', held at Nehru Memorial Museum and Library during June 5-6, 2014.
Keywords: Inscriptions, Indic -- History -- Congresses; Antiquities; Inscriptions, Indic; Kings and rulers; India -- Antiquities -- Congresses; India -- Kings and rulers -- Congresses; India; India; Antiquities; Inscriptions, Indic; Kings and rulers; Conference papers and proceedings; History